Losing the Filipino and the female voice in postcolonial translation how the west has won - Paraan, Lucris Carina A. (2013)
A note from the writer: This paper was initially inspired by the K12 spiral curriculum, where the suggested "literature-based theme" in the seventh grade is given as "Appreciating Myself" under the heading of "Philippine Folk Literature in Translation" (Fermin, 2013). This writer's interest was piqued -- to discover how much of the translated folk literature used by our students is responsive to such a theme. Since Ilocano is a learned second language for this writer, two English translations of Ilocano poems in a popular anthology were chosen for critiquing. Nothing, in the editors' forward, that the purpose of their translations was to follow Filipinos to speak "with one voice that seeks to abnegate the colonial past and claim their distinct cultural identity," this writer used a postcolonial translation framework that puts culture at its axis.
Keywords: Literature and history; Ilocano literature